ANALISIS PENERAPAN E-FAKTUR DALAM PROSEDUR DAN PEMBUATAN FAKTUR PAJAK DAN PELAPORAN SPT MASA PPN PADA CV. WASTU CITRA PRATAMA - Maria, Anzeli; Elim, Inggriani; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
e-Invoice is an electronic tax invoice made by the Directorate General of Taxes to reduce fraud committed by parties who often manipulate tax invoices or create fictitious tax invoices that can affect the VAT to be borne. The implementation of Electronic Tax Invoice is stipulated in the Regulation of the Director General of Taxes PER-16 / PJ / 2014 is conducted gradually starting July 1, 2014, July 1, 2015, and the last July 1, 2016. The purpose of this study was conducted to determine the application of e-invoice in making invoice and to know the application of SPT reporting of VAT Period on CV. Wastu Citra Pratama. The type of research used in this research is descriptive by using qualitative approach. The results showed that in the application of e-Invoice CV. Wastu Citra Pratama has applied e-Invoice since July 2014, the implementation of e-Invoice in the manufacture of tax invoice has been running well, as for some obstacles that often faced the company in using e-Invoice applications can still be overcome only need special attention more, especially in internet networks that are sometimes slow or not supportive so that in uploading tax invoices often fail. In the case of e-Invoice implementation in SPT reporting the VAT period is still the same as before e-Invoice but only in the making is done in one e-Invoicing application. However, in reporting the company uses e-filing and in its reporting is still found a delay in reporting the tax return period of VAT.Keywords: e-Invoice, SPT VAT Period, PER-16/PJ/2014